Vitellogenin transcytosis in follicular cells of the honeybee Apis mellifera and the wasp Polistes simillimus - Dohanik, Virgínia Teles; Gonçalves, Wagner Gonzaga; Oliveira, Leandro Licursi; Zanuncio, José Cola; Serrão, José Eduardo (Protoplasma, 2018)
Vitellogenin receptor (VgR) is a low-density lipoprotein receptor responsible for the mediated endocytosis of vitellogenin (Vg) during egg formation in insects. The maturing oocyte is enveloped by a follicular epithelium, which has large intercellular spaces during Vg accumulation (patency). However, Vg has been reported in the cytoplasm of follicular cells, indicating that there may be a transcellular route for its transport. This study verified the presence of VgR in the follicular cells of the ovaries of the honeybee Apis mellifera and the wasp Polistes simillimus in order to evaluate if Vg is transported via transcytosis in these insects. Antibodies specific for vitellogenin receptor (anti-VgR), vitellogenin (anti-Vg), and clathrin (anti-Clt) were used for immunolocalization. The results showed the presence of VgR on the apical and basal plasma membranes of follicular cells of the vitellogenic follicles in both species, indicating that VgR may have been transported from the basal to the apical cell domain, followed by its release into the perivitelline space, evidenced by the presence of apical plasma membrane projections containing VgR. Co-localization proved that Vg bind to VgR and that the transport of this protein is mediated by clathrin. These data suggest that, in these social insects, Vg is transported via clathrin-mediated VgR transcytosis in follicular cells.
Keywords: Insects; Hymenoptera; Clathrin; Vitellogenesis; Yolk